In vitro pollen culture and the regeneration of Brassica campestris L. plants - Guo, Yang-Dong; Pulli, Seppo (Agricultural Research Centre of Finland, 1995)
Tutkimus sisälsi 28 perimältään erilaista kevätrypsilinjaa ja -lajiketta. Tutkimusmateriaali kasvatettiin alkuvaiheessa kasvihuoneessa ja siirrettiin ennen kukintaa kasvatuskammioon. Mikrosporiviljelyssä parhaan tuloksen tuottivat mikrosporit eli epäkypsät siitepölyhiukkaset, joiden kehitysvaihe oli myöhäinen 1-tumavaihe, mikä edellyttää, että kukkasilmun pituus on 2-4 mm. Oikeassa kehitysvaiheessa olevat kukkasilmut murskattiin B5-nestealustalla ja mikrosporit viljeltiin NLN-nestealustalla, ensin 72 h ajan +32°C:ssa ja seuraavaksi kolme viikkoa +25°C:ssa. Viljellyistä mikrosporeista alkioita tuotti yhdeksäntoista kevätrypsigenotyyppiä. Parhaalla genotyypillä saatiin 100 mikrosporista 300 alkiota. Aktiivihiili 150 mg/l paransi mikrosporien kehitystä ja lakionmuodostusta sekä lisäsi alkioiden lukumäärää. Alkiot kasvatettiin vihreiksi kasveiksi kiinteällä B5-alustalla. Tutkimuksen ensimmäinen vaihe tuotti noin 100 haploidista kevätrypsikasvia.

Brassica campestris (Brassica rapa L. ssp. oleifera) is an important oilseed crop, particularly in Finland. Pollen culture techniques for haploid production have been developed, but B. campestris is relatively recalcitrant in pollen culture. Twenty eight genotypes of B. campestris were included in this study. The donor plants were grown in the greenhouse and transferred to the growth cabinet before bolting. Buds (2-4 mm long) were selected, macerated in B5 medium, then NLN liquid culture medium was added. The microspores were incubated in the dark at 32°C for 72 h, then at 25°C for a further three weeks. Nineteen genotypes produced microspore-derived embryos. The highest yield was more than 300 embryos per 100 buds. Activated charcoal (150 mg/L) promoted embryogenesis, pollen development was faster and the embryo yield was higher. Plants were regenerated after transferring embryos to a solid B5 medium. Colchicine solution was used to double the chromosome complements. About 100 regenerate plants have been obtained in our laboratory, and these haploids will be useful for the oilcrop breeding.
Keywords: Ka; rypsi; kasvinjalostus; oilcrop; genotype; bud size; activated charcoal; donor plant condition; embryogenesis; plant regeneration